Analysis of Formal and Analytic Solutions for Singularities of the Vector Fractional Differential Equations (Analysis in Theory and Applications, 2017)
In this article, we study on the existence of solution for a singularities of a system of nonlinear fractional  differential equations (FDE). We construct a formal power series solution for our considering FDE and prove convergence of formal solutions under conditions. We use the Caputo fractional differential operator and the nonlinearity depends on the fractional derivative of an unknown function.
Keywords: Fractional differential equations; formal power series solution.